The design of requirements modelling languages : How to make formalisms for problem solving in requirements engineering - Jureta, Ivan (Springer International Publishing, 2015)
This book explains in detail how to define requirements modelling languages - formal languages used to solve requirement-related problems in requirements engineering. It moves from simple languages to more complicated ones and uses these languages to illustrate a discussion of major topics in requirements modelling language design. The book positions requirements problem solving within the framework of broader research on ill-structured problem solving in artificial intelligence and engineering in general. Further, it introduces the reader to many complicated issues in requirements modelling language design, starting from trivial questions and the definition of corresponding simple languages used to answer them, and progressing to increasingly complex issues and languages. In this way the reader is led step by step (and with the help of illustrations) to learn about the many challenges involved in designing modelling languages for requirements engineering. The book offers the first comprehensive treatment of a major challenge in requirements engineering and business analysis, namely, how to design and define requirements modelling languages. It is intended for researchers and graduate students interested in advanced topics of requirements engineering and formal language design.